The Study of Plant Microbial Fuel Cell for Alternative Energy Source - Melda Latif; Paskalina Aprila Tiy; Mumuh Muharam; Aulia; Amirul Luthfi (Jurusan Teknik Elektro Universitas Andalas, 2023)
Plant Microbial Fuel Cell (P-MFC) is one of Microbial Fuel Cell type. It can produce electricity and source for plant living. By using the humus soil in the anode chamber, the electron can flow to the cathode chamber. The principle of Plant Microbial Fuel Cell is same with the battery. It flows the direct current. This research makes dual chamber of P-MFC prototype. The salt bridge is used as connection between anode chamber to cathode chamber. The humus soil comes from burning organic waste. Its color is black and contains a lot of microbes. The plant selected in this research was Water Spinach. The number of water spinach were 20 and 25 stems. P-MFC which has more Water Spinach will produce more voltage and current than the others. For 25 Water Spinach, P-MFC produced 762.4 mV no-load average voltage and 125.8 mV, 085 mA for load condition. The result was bigger caused by for more plants will be more microbes resulted in the humus soil.